Effect of carbon-4 and carbon-5 volatile fatty acids inclusion in the substrate varying in protein levels and sources on organic matter and cell wall degradability in vitro - MISRA, A K; THAKUR, S S (The Indian Journal of Animal Sciences, 2013)
Effects of Na-salts of branched chain volatile fatty acids (IB, IV and 2–MB (@ 0.75 and 1.50%) in the substrates containing wheat straw, green fodder and concentrate mixture (40:40:20) and varying in protein content (8, 10 and 12%) and sources (with and without urea) on dry matter, organic matter and cell wall digestion (in vitro) were investigated. Inclusion of BCFA @ 0.75 and 1.50% in the substrate, increased DM, OM and cell wall digestibility compared to control. Higher dose of BCFA (1.50%) did not show any additional advantage. The inclusion of BCFA was most effective in the substrates containing 10 and 12% protein level as the higher in vitro digestion coefficients of DM, OM and cell wall were associated with these protein levels. Among 3 BCFA, the isobutyric acid was most effective in improving the in vitro digestion of DM, OM and cell wall at 24 h, whereas at 48 h, all the 3 BCFA were equally effective. Substrate combinations containing urea showed higher response. Effect of BCFA addition was more pronounced during first 24 h of fermentation compared 48 h. Higher TVFA and acetate concentrations were found associated with the substrate combinations incubated with BCFA. It is evidenced in the study that sodium salt of BCFA has potential to be used as feed supplement with the diets largely based on straw and other crop residues.